2023
DOI: 10.3847/2041-8213/acf7c5
|View full text |Cite
|
Sign up to set email alerts
|

UNCOVER: The Growth of the First Massive Black Holes from JWST/NIRSpec—Spectroscopic Redshift Confirmation of an X-Ray Luminous AGN at z = 10.1

Andy D. Goulding,
Jenny E. Greene,
David J. Setton
et al.

Abstract: The James Webb Space Telescope is now detecting early black holes (BHs) as they transition from “seeds” to supermassive BHs. Recently, Bogdan et al. reported the detection of an X-ray luminous supermassive BH, UHZ-1, with a photometric redshift at z > 10. Such an extreme source at this very high redshift provides new insights on seeding and growth models for BHs given the short time available for formation and growth. Harnessing the exquisite sensitivity of JWST/NIRSpec, here we report the spectroscopic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…NIRSpec IFU observations have revealed broad Hα and Hβ emission lines in a galaxy at z = 5.55 (Übler et al 2023), which is interpreted as a type 1.8 AGN with a black hole mass of M BH ∼ 10 8 M e . Very recently, Larson et al (2023) reported a broad Hβ emission line in a galaxy at z spec = 8.7, suggesting an SMBH whose mass is M BH ∼ 10 7 M e 570 Myr after the Big Bang (see also Bogdan et al 2023;Goulding et al 2023;Greene et al 2023;Fujimoto et al 2023;Kokorev et al 2023;Labbe et al 2023;Maiolino et al 2023;Matthee et al 2023 for studies that appeared after our initial submission of this paper).…”
Section: Introductionmentioning
confidence: 93%
“…NIRSpec IFU observations have revealed broad Hα and Hβ emission lines in a galaxy at z = 5.55 (Übler et al 2023), which is interpreted as a type 1.8 AGN with a black hole mass of M BH ∼ 10 8 M e . Very recently, Larson et al (2023) reported a broad Hβ emission line in a galaxy at z spec = 8.7, suggesting an SMBH whose mass is M BH ∼ 10 7 M e 570 Myr after the Big Bang (see also Bogdan et al 2023;Goulding et al 2023;Greene et al 2023;Fujimoto et al 2023;Kokorev et al 2023;Labbe et al 2023;Maiolino et al 2023;Matthee et al 2023 for studies that appeared after our initial submission of this paper).…”
Section: Introductionmentioning
confidence: 93%
“…For the first time, it is possible to observe galaxies and candidates spanning 0.2  z  15 and infer their stellar population properties. In the context of UNCOVER, spectroscopically confirmed galaxies at z > 12 and an X-ray luminous supermassive black hole at z = 10.1 are studied in detail in Wang et al (2023a) and Goulding et al (2023), respectively, whereas a systematic search for z spec  9 sources is carried out in Fujimoto et al (2023b). The core of this paper is to present a galaxy catalog containing key stellar population metrics over the full dynamic range probed by the survey.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of faint AGN have also been identified at z ∼ 4-7 (e.g., Harikane et al 2023;Kocevski et al 2023;Maiolino et al 2023a;Matthee et al 2023;Onoue et al 2023;Übler et al 2023), with steeper faint ends in their luminosity functions than expected from extrapolating previous results. Such candidates are also detected out to higher redshifts, z ∼ 9-12 (Fudamoto et al 2022;Goulding et al 2023;Larson et al 2023;Maiolino et al 2023b). Recently, the EPOCHS survey covering the JWST PEARLS and Early Release Observations (EROs) fields identified nine new AGN in the 6.5 < z < 12 redshift range (Juodžbalis et al 2023), and the UNCOVER survey used the JWST NIRSpec to provide the UV luminosity functions from 15 AGN candidates over z ∼ 4-8 (Greene et al 2023).…”
Section: Introductionmentioning
confidence: 90%